POTRET RASULULLAH SEBAGAI PENDIDIK - Usiono Usiono (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
ABSTRACT Know the portrait of the Messenger of Allah. As an educator is a necessity because of the education given by the Prophet. Contains the spirit and spirit of building people in a much better direction. In the view of Islam, the position of educators is very important. Without the presence of educators, the educational process does not mean anything. Therefore, to realize educators who have the spirit (spirit) of Islam, need to see the side of life or characteristics of the Prophet. As an educator, because the essence of his sending him as the Messenger of Allah on earth is as uswah al-Hasanah and rahmatan lil 'alamin. That is, all aspects of the sunnah of the Prophet. Is the ultimate guide after the Qur'an in all aspects of human life, including aspects of education. Its existence as an educator is the source of educational concepts that the truth is recommended by Allah swt. In terms of education of the Holy Prophet. Has provided many lessons for educators regarding educational methods, which can be implemented by educators in formal institutions (schools) and at home by parents who provide education to their children. Keywords: Rasulullah, Method, Teacher